2015
DOI: 10.1002/lsm.22413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light-emitting diode irradiation on RANKL-induced osteoclastogenesis

Abstract: Taken together, the results presented herein show that LED irradiation downregulates osteoclastogenesis by reducing ROS production. Therefore, LED irradiation/LLLT might be useful as an alternative, conservative approach to osteoporosis management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 37 publications
(44 reference statements)
1
13
0
Order By: Relevance
“…To date, only a handful of studies have evaluated the effects of PBM on Nrf2 expression and activity. Interestingly, Sohn et al reported an increase in Nrf2 gene expression following irradiation at 635 nm (140). Similarly, Trotter et al also found that application of blue light induced significant increases in Nrf2 expression in vitro (141).…”
Section: Nuclear Factor Erythroid 2-related Factor 2 (Nrf2) Signallingmentioning
confidence: 99%
“…To date, only a handful of studies have evaluated the effects of PBM on Nrf2 expression and activity. Interestingly, Sohn et al reported an increase in Nrf2 gene expression following irradiation at 635 nm (140). Similarly, Trotter et al also found that application of blue light induced significant increases in Nrf2 expression in vitro (141).…”
Section: Nuclear Factor Erythroid 2-related Factor 2 (Nrf2) Signallingmentioning
confidence: 99%
“…The use of LED irradiation in PBT has already been determined in terms of its positive role in the stimulation of neuronal growth, post‐ischemia skeletal muscle protective effects, protection of cardiomyocytes, acceleration of wound healing, reduction of the inflammatory response, and cellular proliferation and differentiation . In this study, it has been determined that red LED irradiation also has an effect on hepatocyte proliferation.…”
Section: Discussionmentioning
confidence: 92%
“…Photobiomodulation therapy modulates cell function mainly through the photoreceptors existing in cells that can achieve activation transformation after absorbing the energy of light, including metabolism, mitosis, and apoptosis. Ulteriorly, it achieves biological effects, such as promoting wound healing, neurite growth acceleration, and the increase of stem cell differentiation . Different from short‐wavelength visible light, which mainly correlates to cell apoptosis, red light can be specifically absorbed by cytochrome c oxidase, and which plays an essential role in mitochondrial respiration and electron transport, increasing adenosine triphosphate and reactive oxygen species (ROS) production and affecting various biological processes .…”
Section: Introductionmentioning
confidence: 99%
“…Beyond its effects on osteoblasts, some studies have also demonstrated the potential of PBM to inhibit osteoclastogenesis [41,42]. Reduced ROS production has been proposed as a possible cause of reduced osteoclastogenesis following irradiation [4143]. Moreover, many studies found that PBM could promote bone healing and improve bone quantity and strength in ovariectomized rats [39,40,4446], in which near infrared light was more commonly used.…”
Section: Discussionmentioning
confidence: 99%